DECISION MAKING SYSTEMS FOR THE PERFORMANCE MEASUREMENT OF THE COVID-19 TASK FORCE IN PAGELARAN DISTRICT USING THE COMPARISON OF THE SIMPLE ADDITIVE WEIGHTING (SAW) METHOD AND THE WEIGHTED PRODUCT (WP) METHOD - Komariyah Komariyah; Muhamad Muslihudin (International Journal of Artificial Intelligence and Robotic Technology (IJAIRTec), 2022)
Coronavirus is a virus which originated in Wuhan, China because this virus was first discovered in Wuhan, China. The spread is very fast. According to the prevention manual, Coronavirus Disease (COVID-19) is clarified into 3, patients under surveillance, people under monitoring and people without symptoms. This virus entered Indonesia on March 2, 2020. In order to reduce the spread of the corona virus-19, the government is expected to be able to form a disciplined and best Covid-19 task force team. To determine the best task force team, it must follow the criteria which have been set with the best performance gets a reward or award. In measuring the performance of the Covid-19 task force towards the predetermined criteria, a decision-making system is used by using a comparison of the simple additive weighting method and the weighted product method, which in this method looks for the weighted summation of the performance branches on each alternative on each criterion on all attributes. The criteria for the productivity aspect describe supervision, socialization, and appeals. The criteria for service quality aspects explain the existence of information disclosure in conducting monitoring. The criteria for the quality aspect of human resources explain the direction and training in developing leadership. Responsiveness aspect criteria explain about the quick handling as well as health services and the provision of social assistance. The responsibility criteria explain the work procedures of the COVID-19 task force. The criteria for the accountability aspect explain the reporting of work and financial evaluations. The management aspect criteria describe project development. Criteria for field operation aspects explain the acceleration of handling and the capacity of health workers. By using these criteria and by using a comparison between the simple additive weighting (saw) and weighted product (wp) methods, it can be seen that the performance weight value of the COVID-19 task force in Pagelaran District, Pringsewu Lampung with the best results according to the specified criteria, is 92 and 0.14.